2013
DOI: 10.1097/nen.0b013e318293eb08
|View full text |Cite
|
Sign up to set email alerts
|

Mediation of Protection and Recovery From Experimental Autoimmune Encephalomyelitis by Macrophages Expressing the Human Voltage-Gated Sodium Channel NaV1.5

Abstract: Multiple sclerosis (MS) is the most common nontraumatic cause of neurologic disability in young adults. Despite treatment, progressive tissue injury leads to accumulation of disability in many patients. Here, our goal was to develop an immune-mediated strategy to promote tissue repair and clinical recovery in an MS animal model. We previously demonstrated that a variant of the voltage-gated sodium channel NaV1.5 is expressed intracellularly in human macrophages, and that it regulates cellular signaling. This c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The intracellular Na V 1.5 channel was shown to enhance endosomal acidification and phagocytosis (Carrithers et al, 2007), Ca 2+ signaling, and phenotypic differentiation in human macrophages (Carrithers et al, 2011). The same group later demonstrated that SCN5A was expressed as a new splice variant lacking exon 25, resulting in a deletion of 18 amino acids in domain III (Rahgozar et al, 2013), generating non-selective outward currents and small inward currents in a heterologous expression system (Jones et al, 2014).…”
Section: Na V a And Na V B Subunits In Leukemia Cellsmentioning
confidence: 98%
“…The intracellular Na V 1.5 channel was shown to enhance endosomal acidification and phagocytosis (Carrithers et al, 2007), Ca 2+ signaling, and phenotypic differentiation in human macrophages (Carrithers et al, 2011). The same group later demonstrated that SCN5A was expressed as a new splice variant lacking exon 25, resulting in a deletion of 18 amino acids in domain III (Rahgozar et al, 2013), generating non-selective outward currents and small inward currents in a heterologous expression system (Jones et al, 2014).…”
Section: Na V a And Na V B Subunits In Leukemia Cellsmentioning
confidence: 98%
“…Because of an exon deletion in the extracellular selectivity filter, channel activation does not elicit typical action potentials as in excitable tissues but does mediate ionic flux in response to pharmacological stimulation. Because this channel is not expressed in murine macrophages, in vivo characterization has been performed in a knock-in transgenic model (7).…”
mentioning
confidence: 99%
“…In this context, SCN5A inhibitors may contribute to controlling both systemic inflammation and viral infection. Other studies reported that macrophages present an anti-inflammatory phenotype in mice expressing human SCN5A [70] .…”
Section: Discussionmentioning
confidence: 91%